2018
DOI: 10.4103/abr.abr_91_18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa Extracts on the Lipid Profile and Uncoupling Protein-1 Gene Expression in Brown Adipose Tissue of Mice

Abstract: Background:Uncoupling protein-1 (UCP-1) is the index protein of the brown adipose tissue (BAT), used in the obesity studies. We evaluated the effects of thymoquinone (TQ), hydroalcoholic, and hexane extracts of Nigella sativa, on the UCP-1 gene expression in BAT, and also on the recovery from oxidative stress, due to a high-fat diet.Materials and Methods:Fifty mice were divided into five groups: the first group was fed with a usual diet and the second, third, fourth, and fifth groups with a high-fat diet, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In this regard, the results of a study showed that the use of Nigella sativa significantly reduced levels of total cholesterol, LDL, and triglyceride (23). It has also been reported that the use of Nigella sativa reduces levels of cholesterol and triglyceride (24). In traditional books, Nigella sativa used to treat hyperlipidaemia, which is consistent with the findings of the present study (25).…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the results of a study showed that the use of Nigella sativa significantly reduced levels of total cholesterol, LDL, and triglyceride (23). It has also been reported that the use of Nigella sativa reduces levels of cholesterol and triglyceride (24). In traditional books, Nigella sativa used to treat hyperlipidaemia, which is consistent with the findings of the present study (25).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies suggest that N. sativa oil and extracts have antioxidant properties and can modulate oxidative stress, which could be beneficial for oxidative stress related diseases/disorders. In this sense, oils and solvent extracts from N. sativa seeds possessed antioxidant activity in vitro ( Toma et al, 2015 ; Mohammed et al, 2016 ; Abedi et al, 2017 ; Singhal et al, 2017 ), ex vivo ( Ghoreyshi et al, 2020 ), in vivo ( Mahmoudi et al, 2018 ; Rasoli et al, 2018 ) and in humans ( Nikkhah-Bodaghi et al, 2019 ). Moreover, in vivo regular intake of ethanolic extract of N. sativa seed (400 mg/kg) lowered the lipid peroxidation, and enhanced catalase activity in Wistar rats ( Rasoli et al, 2018 ).…”
Section: Biological Activities: Preclinical In Vitro/in Vivo Studies Of the Genus Nigella And Activmentioning
confidence: 99%
“…Another work suggested that hydroalcoholic and hexane extracts of N. sativa seed as well as thymoquinone may counteract oxidative stress caused by high-fat diets (HFDs), e.g. malondialdehyde (MDA) levels decreased, while the activity of catalase enzyme and serum total antioxidant capacity increased ( Mahmoudi et al, 2018 ). Concerning other Nigella species, N. damacena 70% ethanolic extract (seeds) has shown antioxidant properties in vitro , even higher generally than N. sativa seeds ( Toma et al, 2015 ); the former contained higher amounts of quercetin derivatives.…”
Section: Biological Activities: Preclinical In Vitro/in Vivo Studies Of the Genus Nigella And Activmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have highlighted that N. sativa oil has anti-inflammatory, anti-oxidant, immunomodulatory, and anti-cancer activities [2,3]. Recently, other investigations have addressed the possibility that N. sativa oil improves glucose homeostasis and lipid profile [4,5]. Additionally, pharmacological studies have highlighted that N. sativa oil can have gastroprotective, hepatoprotective, antitussive, cardioprotective, and anti-hypertensive properties [1].…”
Section: Introductionmentioning
confidence: 99%